Adapting to Teaching and Learning During Covid-19: A Case of Islamic School's Initiative of Self-regulated Learning - Mustajab Mustajab; Hasan Baharun; Zakiyah Fawa’iedah (FITK UIN Walisongo, 2020)
This study aims to analyze self-regulated learning in Islamic education amid the Covid-19 pandemic. This study incorporates a qualitative approach to understand self-regulated learning at Miftahul Ulum Islamic High School, East Java. The data collection techniques consist of teachers' interviews, teaching and learning observation, and documentation. The results showed that implementing self-regulated learning during the Covid 19 pandemic was carried out online through activities, analysis of learning conditions, determining the learning design, applying strategies, and evaluation. Despite challenges, online self-regulated learning facilitates Miftahul Ulum Islamic School students to participate in learning activities during the Covid-19 Pandemic.